Blueberry Pectin Extraction Methods Influence Physico‐Chemical Properties. Issue 12 (21st November 2018) - Koh, Jeewon; Xu, Zhimin; Wicker, Louise
Abstract : Abstract: Pectins from highbush blueberry powder were sequentially solubilized in water, chelator, and sodium carbonate solvents and precipitated (ADF.WSF, ADF.CSF, and ADF.NSF) or not precipitated in ethanol (DF.WSF, DF.CSF, and DF.NSF) before dialysis and freeze‐drying. Alcohol precipitation more effectively removed bound anthocyanins and low molar mass pectins from water‐ and chelator soluble fractions than dialysis alone. Blueberry water soluble fractions were high methoxyl pectins, rich in neutral sugars (36 to 38 mol%), and had high molar mass (7.01 × 10 5 to 2.71 × 10 6  g/mol). Blueberry chelator soluble fractions were low methoxyl pectins and rich in uronic acids (90 to 92 mol%) which were more linear and less branched structure than other fractions or commercial citrus pectin. The molar mass ranged from 1.59 × 10 6 to 2.06 × 10 6  g/mol. Water‐ and chelator soluble fractions exhibited pseudoplastic behavior ( n  < 1) at 1% dispersion. Blueberry sodium carbonate soluble fractions were rich in protein (18%) and neutral sugars (42 to 28 mol%), and had low molar mass (1.08 × 10 5 to 1.27 × 10 5  g/mol). Blueberry pectins have desirable physico‐chemical properties for use as functional ingredients in food or beverages. Practical Application: Alcohol precipitation effectively removed anthocyanins from the pectin. The characterization data provided the benefits of blueberry pectin as a functional ingredient. This study can be used by food or product developers who are interested in pectin from blueberries or other berry products.